2023
DOI: 10.1111/omi.12408
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cetylpyridinium Chloride mouthwash against SARS‐CoV‐2: A systematic review of randomized controlled trials

Abstract: Introduction COVID‐19 is a transmissible respiratory and multisystem disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Viral transmission occurs mainly through the spread of salivary droplets or aerosol from an infected subject. Studies suggest that salivary viral load is correlated with disease severity and probability of transmission. Cetylpyridinium chloride mouthwash has been found to be effective in reducing salivary viral load. The aim of this systematic review of randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…All in all, our results confirm the antiviral properties of CPC and CHX against IAV and include RSV as a susceptible microorganism to these two compounds. Given these results, the data available in the literature [5,8,9,11,[13][14][15][19][20][21]34], and the mechanisms of action of both CPC and CHX [10,22,[35][36][37][38] we could expect similar results for other enveloped respiratory viruses.…”
Section: Plos Onesupporting
confidence: 66%
See 1 more Smart Citation
“…All in all, our results confirm the antiviral properties of CPC and CHX against IAV and include RSV as a susceptible microorganism to these two compounds. Given these results, the data available in the literature [5,8,9,11,[13][14][15][19][20][21]34], and the mechanisms of action of both CPC and CHX [10,22,[35][36][37][38] we could expect similar results for other enveloped respiratory viruses.…”
Section: Plos Onesupporting
confidence: 66%
“…Additionally, CPC has demonstrated antiviral activity against some enveloped viruses, including common human coronaviruses [12], Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV 2) [13][14][15][16], Middle East Respiratory Syndrome virus (MERS) [17,18], and influenza virus [19]. Furthermore, mouthwash formulations containing CPC reduced cold symptoms in randomized placebo-controlled double-blind trials [20,21]. The positively charged "head" on CPC interacts with negatively charged lipids on the surface of biological membranes, both of viral or bacterial origin.…”
Section: Introductionmentioning
confidence: 99%
“…Tarrago-Gil et al initiated a clinical trial to detect SARS-CoV-2 in saliva of COVID-19 patients 2 h after using 0.07% CPC mouthwash or placebo, and the results showed that virus lysis in saliva of patients was significantly increased after CPC mouthwash intervention [20]. D'Amico et al conducted a systematic review of 6 randomized controlled studies involving 301 participants, results of which suggested that, compared to the group of placebo and other mouthwash ingredients, CPC suggested favorable effectiveness [21]. Besides, this systematic review also indicated that CPC alone can eradicate SARS-CoV-2, while some substances of mouthwash product, such as benzoate, possibly even blunt the CPC effects.…”
Section: In Vitro Cytotoxicity and Antiviral Activitymentioning
confidence: 99%
“…Essential oils containing mouthwashes due to their antimicrobial and anti-inflammatory properties are commonly used since their usage is not time limited [8]. Cetylpyridinium chloricum (CPC) containing mouth rinses gained popularity recently due to its effectiveness during the COVID-19 pandemic [13]. Its adjunctive use in dentistry had limited effects in controlling plaque accumulation and gingivitis levels, with no adverse microbiological or tissue effects [14].…”
Section: Introductionmentioning
confidence: 99%